2021
DOI: 10.3389/fsoil.2021.706701
|View full text |Cite
|
Sign up to set email alerts
|

Improved Wetland Soil Organic Carbon Stocks of the Conterminous U.S. Through Data Harmonization

Abstract: Wetland soil stocks are important global repositories of carbon (C) but are difficult to quantify and model due to varying sampling protocols, and geomorphic/spatio-temporal discontinuity. Merging scales of soil-survey spatial extents with wetland-specific point-based data offers an explicit, empirical and updatable improvement for regional and continental scale soil C stock assessments. Agency-collected and community-contributed soil datasets were compared for representativeness and bias, with the goal of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
(48 reference statements)
0
10
1
Order By: Relevance
“…Our estimate of carbon stock in the Histosols of coastal Louisiana at 0–1 m depth (33.2 ± 0.6 kg C m −2 ) was greater than the values reported by Unran et al. (2021) (27 kg C m −2 ) but smaller than the values reported by Nahlik and Fennessy (2016) (33.2 ± 0.6 kg C m −2 ) for tidal marshes (Histosols) of the conterminous United States. Limited carbon stock data for depths below 1 m is available in the literature indicating the need for deeper (>1 m) carbon profile studies.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Our estimate of carbon stock in the Histosols of coastal Louisiana at 0–1 m depth (33.2 ± 0.6 kg C m −2 ) was greater than the values reported by Unran et al. (2021) (27 kg C m −2 ) but smaller than the values reported by Nahlik and Fennessy (2016) (33.2 ± 0.6 kg C m −2 ) for tidal marshes (Histosols) of the conterminous United States. Limited carbon stock data for depths below 1 m is available in the literature indicating the need for deeper (>1 m) carbon profile studies.…”
Section: Resultscontrasting
confidence: 87%
“…We found increasing wetland soil carbon content with increased depth in the northern part of Barataria Bay, Louisiana. Generally, carbon stored in 1 m soil depth has been considered in the carbon stock of the Histosols in tidal marshes (Nahlik & Fennessy, 2016; Unran et al., 2021). However, the carbon stock in the total 2 m depth of Barataria Bay wetlands was ∼88% greater than the carbon stock in 1 m soil depth alone.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite their shared vegetation type and hydrogeomorphic class (depressional), as well as their proximity to one another, the 19 forested wetlands we sampled had SOC stocks spanning values characteristic of mineral wetlands (∼20 kg C m −2 ) to those of organic wetlands (>50 kg C m −2 ; table 4). Mean stocks in our forested wetlands were 32.2 ± 8.4 kg m −2 ; in comparison, a recent analysis of 529 inland wetlands, which spanned vegetation types and ecoregions throughout [115] the conterminous US, estimated mean SOC stocks at 19.7 ± 10.6 kg m −2 [90]. We compiled a list of relevant studies encompassing a range of wetland types and found that high within-type variability is common 4).…”
Section: High Natural Variability In Wetland Soc Stocksmentioning
confidence: 69%
“…However, many forested wetlands remain mis-classi ed as upland forest due to di culty in con rming soil moisture conditions due to dense canopies that obscure surface features from remote imagery. We suggest that there is signi cant potential to improve on previous work from Nahlik and Fennessey, 11 and Uhran et al, 12 , the latter of which was used for the wetland SOC baseline comparison in this study. 55 and our analysis supports improving SOC estimates with new approaches using probabilistic models that better re ect the spatial distribution of soil moisture conditions.…”
Section: Comparisons To Other Soc Mapping Studiesmentioning
confidence: 82%
“…In total we used 300 bootstrapped SOC prediction maps where each pixel contained 300 predictions to simulate a distribution from which we extracted the standard deviation to represent the prediction interval uncertainty. We then compared the WIP wetland SOC stocks with 1m SOC stocks from the National Wetland Condition Assessment (NWCA) 12 . Uhran et al, provides the latest mapped wetland SOC stocks at 1 m depths for the continental U.S. modeled from harmonized pedon data from NWCA and mapped using the NLCD wetland extents at a 30 m resolution.…”
Section: Soc Stock Predictionmentioning
confidence: 99%